How to survive: Artificial quality food schemes and new forms of rule for farmers in direct marketing strategies. (August 2018) - Argüelles, Lucía; Anguelovski, Isabelle; Sekulova, Filka
Highlights: Quality food schemes ascribe superiority to products, allowing producers to get premium prices or sell to exclusive markets. The entrepreneurial logics and the focus on quality for the benefits of urban customers bring new challenges to producers. · While the programs use a discourse of urban-rural reconnection, they embed top-down and unbalanced politics. The quality strategy seems imposed, and the created quality foods result artificial. Results call for a more nuanced perspective of the alternatives to the mainstream agri-food system.